Virion proteomics of genetically intact HCMV reveals a regulator of envelope glycoprotein composition that protects against humoral immunity - Kirsten Bentley; Evelina Statkute; Isa Murrell; Ceri A. Fielding; Robin Antrobus; Hannah Preston; Lauren Kerr-Jones; Daniel Cochrane; Ilija Brizic; Paul J. Lehner; Gavin W. G. Wilkinson; Eddie C. Y. Wang; et al. (Proceedings of the National Academy of Sciences, 2025)
Human cytomegalovirus (HCMV) is a clinically important herpesvirus that has coevolved for millions of years with its human host, and establishes lifelong persistent infection. A substantial proportion of its 235 kb genome is dedicated to manipulating host immunity through targeting antiviral host proteins for degradation or relocalization. Quantitative proteomics of the infected cell has extensively characterized these processes, but the cell-free virion has been less well studied. We therefore carried out proteomic analysis of a clinical HCMV strain (Merlin) virion. This revealed 18 novel components, including the viral protein gpUL141, which is recognized as an NK immune-evasin that targets several host proteins (CD155, CD112, and TRAILR) when expressed within the cell. Coimmunoprecipitation of gpUL141 from virions identified interactions with viral entry glycoproteins from the trimer (gH/gL/gO), pentamer (gH/gL/UL128/UL130/UL131A), and gH/gpUL116 complexes, as well as gB. Only interactions with gH/gB occurred in the absence of other viral proteins. Analysis supported a model in which gpUL141 homodimers independently interacted with separate gB/gH-containing complexes. gpUL141 encodes an ER retention domain that restricts trafficking through the ER/Golgi, and limited the transport of glycoprotein complexes bound by gpUL141. As a result, gpUL141 reduced levels of multiple glycoprotein complexes on the infected cell surface as well as in the virion. This reduced syncytium formation, inhibited antibody-dependent cellular cytotoxicity (ADCC), and reduced susceptibility to neutralizing antibodies. Thus, gpUL141 represents an immune-evasin that not only targets host proteins to limit NK-cell attack, but also alters the trafficking of multiple viral glycoprotein complexes in order to evade humoral immunity.